Activation of ERK2 in basolateral amygdala underlies the promoting influence of stress on fear memory and anxiety: Influence of midazolam pretreatment - Maldonado, Noelia Martina (2013)
Exposure to emotionally arousing experiences elicits a robust and persistent memory and enhances anxiety. The amygdala complex plays a key role in stress-induced emotional processing and in the fear memory formation. It is well known that ERK activation in the amygdala is a prerequisite for fear memory consolidation. Moreover, stress elevates p-ERK2 levels in several areas of the brain stress circuitry. Therefore, given that the ERK1/2 cascade is activated following stress and that the role of this cascade is critical in the formation of fear memory, the present study investigated the potential involvement of p-ERK2 in amygdala subnuclei in the promoting influence of stress on fear memory formation and on anxiety-like behavior. A robust and persistent ERK2 activation was noted in the Basolateral amygdala (BLA), which was evident at 5 min after restraint and lasted at least one day after the stressful experience. Midazolam, a short-acting benzodiazepine ligand, administered prior to stress prevented the increase in the p-ERK2 level in the BLA. Pretreatment with intra-BLA infusion of U0126 (MEK inhibitor), but not into the adjacent central nucleus of the amygdala, attenuated the stress-induced promoting influence on fear memory formation. Finally, U0126 intra-BLA infusion prevented the enhancement of anxiety-like behavior in stressed animals. These findings suggest that the selective ERK2 activation in BLA following stress exposure is an important mechanism for the occurrence of the promoting influence of stress on fear memory and on anxiety-like behavior.